The Image of the Catholic church in the Yugoslav press in the period of Yugoslav authorities’ efforts to break the relations with the Holy See (1952) - Wawryszuk, Paweł (Balcanica Posnaniensia. Acta et studia, 2021)
The aim of the article is to analyse the actions taken by the Yugoslav press against the Catholic Church. The beginning of this campaign may be dated from the middle of January 1952. During the meeting of the Executive Bureau of the Central Committee of the Communist Party of Yugoslavia, Josip Broz Tito decided the break diplomatic relations with the Holy See. The press campaign focused mostly on Croatia and Slovenia, the republics with the majority of the Catholic population. The Catholic church was presented as an anti-Yugoslav factor, and the Yugoslav Catholic hierarchy and its leaders, including a head of the church, Croatian bishop Alojzije Stepinac were accused of being collaborators of the fascist regimes from the war period. On the other hand, the press avoided attacks on lower rank priests, hoping to convince them to join the pro-government associations.